Táj és ember viszonya: Biológiai burjánzás Szentkuthy Miklós Fejezet a szerelemről című regényében - Kerber, Balázs (Studia Litteraria, 2023)
In this paper I will focus mainly on the biopoetic aspects of Miklós Szentkuthy’s novel, Chapter on Love. In his novel, Szentkuthy creates an intense rhetorical web of biological metaphors and imagery, also elaborates a specific literary language, a unique world of fiction, in which the boundaries between man and nature are blurred or, on the contrary, even sharpened. e novel, like many of Szentkuthy’s works, uses a theoretical, philosophical vision to approach the experience of elementary perception. I examine the narrator’s interpretation of the individual’s relationship to the larger biological processes, and how the text creates a kind of visual and rhetorical forest.